O23 Can children swallow tablets? outcome data from a feasibility study to assess the swallowability and acceptability of different sized placebo tablets in children and young people (creating acceptable tablets – cat). Issue 6 (17th May 2019) - Bracken, L; McDonough, E; Ashleigh, S; Wilson, F; Ohia, U; Mistry, P; Jones, H; Kanji, N; Liu, F; Peak, M
Abstract : Background: It can be challenging to administer medicines to children and young people (CYP); due to the lack of available age-appropriate formulations. Developing medicines that are acceptable to CYP has the potential to improve treatment outcomes. 1 Acceptability has been defined as 'an overall ability of the patient and caregiver (defined as 'user') to use a medicinal product as intended'. 2 There is limited evidence for the acceptability of tablets in CYP. This feasibility study aimed to investigate the swallowability and acceptability of different sized placebo tablets in CYP aged 4–12. Method: Participants were asked to swallow three different sized placebo tablets; 6 mm, 8 mm and 10 mm, smallest to largest. Both healthy children and NHS patients were recruited. The researcher observed and recorded children's facial expressions as they swallowed each tablet. 3 Following administration, an internal inspection of the mouth was conducted to identify any residue or non-swallowed tablet. 4 Participants completed a questionnaire about the acceptability of each tablet. For analysis participants were stratified by age: 4–8 and 9–12 years. Results: 55 participants were recruited to the study. 30 children were in the younger group, of which 23% had taken a tablet before. 84% of the 25 older children had previously taken a tablet. 100% of participants attempted to swallow the 6mm tablet, with 67% of younger children and all older children successfully swallowing the tablet. All participants in the older group attempted to swallow the 8 mm and 10 mm tablet with 100% successfully swallowing the 8 mm and 96% successfully swallowing the 10 mm tablet. 77% of younger children attempted to swallow the 8 mm tablet, with 91% succeeding. 70% of younger children attempted the 10mm tablet, with 95% succeeding. Conclusion: This study demonstrates that tablets of 6mm, 8mm and 10mm are potentially an acceptable formulation for children aged 4–12 years. References: Venables R, Batchelor HK, Hodson J, Stirling H, Marriott J. Determination of formulation factors that affect oral medicines acceptability in a domiciliary paediatric population. Int J Pharm 2015;480(1–2):55–62. Kozarewicz P. Regulatory perspectives on acceptability testing of dosage forms in children. Int J Pharm 2014;469:245–8. doi:10.1016/j.ijpharm.2014.03.057. European Medicines Agency. Guideline on pharmaceutical development of medicines for paediatric use. 2013;44:1–24. Zeinstra GG, Koelen MA, Colindres D, et al. Facial expressions in school-aged children are a good indicator of 'dislikes'but not of 'likes'. Food Quality and Preference 2009 December 2009;20(8):620–624. Klingmann V, Spomer N, Lerch C, et al. Favorable Acceptance of Mini-Tablets Compared with Syrup: A Randomized Controlled Trial in Infants and Preschool Children. The Journal of Pediatrics 2013 December 2013;163(6):1728–1732.e1. Disclosure(s): Nothing to disclose